Time Course of Immune Response and Immunomodulation During Normal and Delayed Healing of Musculoskeletal Wounds - Muire, Preeti J.; Mangum, Lauren H.; Wenke, Joseph C. (Frontiers in Immunology, 2020)
Single trauma injuries or isolated fractures are often manageable and generally heal without complications. In contrast, high-energy trauma results in multi/poly-trauma injury patterns presenting imbalanced pro- and anti- inflammatory responses often leading to prolonged inflammation. These injuries often exhibit delayed healing, leading to fibrosis of injury sites and delayed healing of fractures depending on the intensity of the compounding traumas. Prolonged inflammation is accompanied by a temporal shift in the innate and adaptive immune cells distribution, triggered by the overwhelming release of an arsenal of inflammatory mediators such as complements, cytokines and damage associated molecular patterns (DAMPs) from necrotic cells. Recent studies have implicated this prolonged and dysregulated inflammation in the poor prognosis of polytraumatic injuries, however, interventions focusing on immunomodulating inflammatory cellular composition and activation, if administered incorrectly, can result in immune suppression and unintended outcomes. Immunomodulation therapy is promising but should be conducted with consideration for the spatial and temporal distribution of the immune cells during impaired healing. This review describes the current state of knowledge in the spatiotemporal distribution patterns of immune cells at various stages during musculoskeletal wound healing, with a focus on recent advances in the field of Osteoimmunology, a study of the interface between the immune and skeletal systems, in long bone fractures. The goals of this review are to 1) discuss wound and fracture healing processes of normal and delayed healing in skeletal muscles and long bones; 2) provide a balanced perspective on temporal distributions of immune cells and skeletal cells during healing; and 3) highlight recent therapeutic interventions used to improve fracture healing. This review is intended to promote an understanding of the importance of inflammation during normal and delayed wound and fracture healing. Knowledge gained will be instrumental in developing novel immunomodulatory approaches for impaired healing.